Expediting the management of cauda equina syndrome in the emergency department through clinical pathway design. Issue 4 (2nd November 2019) - Buell, Kevin G; Sivasubramaniyam, Sujan; Sykes, Mark; Zafar, Kamran; Bingham, Lucy; Mitra, Anu
Abstract : Introduction: Cauda equina syndrome (CES) is a neurosurgical emergency. Early diagnosis with MRI and subsequent surgical decompression surgery can prevent permanent neurological dysfunction. Charing Cross Hospital (CXH) is a tertiary neurosurgical referral centre where in the emergency department (ED), current practice mandated a neurosurgery review prior to requesting MRI. Hypothesis: It was hypothesised that a new clinical pathway, with better coordination from the ED, radiology and neurosurgical teams could reduce the time of presentation to diagnosis or exclusion of CES. Method: Retrospective case-note analysis of patients presenting with back pain to CXH ED over a 3-month period was performed. The primary outcome was the time interval between the patient's arrival to the ED and the MRI preliminary report. Results: The baseline primary outcome was recorded at 8 hours and 16 min (n=30). A new clinical pathway was designed empowering ED senior decision makers to order MRIs prior to neurosurgical review. Two Plan-Do-Study-Act (PDSA) cycles were performed, each measured over a 2-month period. The first PDSA cycle was performed after the pathway was initially launched (n=17), while the second PDSA cycle measured the effect of staff education and active promotion of the pathway (n=17). MRI was requested earlier, waiting and reporting time for MRI were reduced. The exclusion or diagnosis of CES was reduced to 5 hours and 54 min in PDSA 1 and 5 hours 17 min in PDSA 2, a 29% and 36% reduction (p=0.048 and p=0.012, respectively). Conclusion: The clinical protocol was a cost-neutral and sustainable intervention that effectively reduced the time taken to diagnose or exclude CES and ED waiting times.